2018
DOI: 10.1096/fj.201801749rrr
|View full text |Cite
|
Sign up to set email alerts
|

Optineurin inhibits NLRP3 inflammasome activation by enhancing mitophagy of renal tubular cells in diabetic nephropathy

Abstract: Tubulointerstitial inflammation plays a critical role in the progression of diabetic nephropathy (DN), and nucleotide‐binding oligomerization domain‐like receptor family pyrin domain‐containing 3 (NLRP3) inflammasomes contribute to renal interstitial inflammation in DN. Decreased expression of optineurin (OPTN) is also associated with the progression of DN. We investigated the role of OPTN in activation of the NLRP3 inflammasome in DN. We initially examined the renal biopsy tissues of 172 patients with type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 57 publications
(58 reference statements)
0
44
0
Order By: Relevance
“…The NLRP3 inflammasome activated in sepsis or myocardial mitochondrial stress was also eliminated by mitophagy [[32], [33], [34]]. In kidney research, Chen and colleagues demonstrated that optineurin induced mitophagy to inhibit the activation of NLRP3 in DKD [25]. Xu et al showed that prohibitin 2-induced mitophagy inhibited the NLRP3 inflammasome in CKD, through amelioration of mitochondrial dysfunction [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLRP3 inflammasome activated in sepsis or myocardial mitochondrial stress was also eliminated by mitophagy [[32], [33], [34]]. In kidney research, Chen and colleagues demonstrated that optineurin induced mitophagy to inhibit the activation of NLRP3 in DKD [25]. Xu et al showed that prohibitin 2-induced mitophagy inhibited the NLRP3 inflammasome in CKD, through amelioration of mitochondrial dysfunction [35].…”
Section: Discussionmentioning
confidence: 99%
“…HK-2 cells were cultivated in DMEM/F-12 (ThermoFisher Scientific, 11330057) with 10% foetal bovine serum (ThermoFisher Scientific, 10099158). Transient transfections of HK-2 cells with siRNA (50 nM) were performed by Lipofectamine™ 3000 Transfection Reagent (ThermoFisher Scientific, L3000150) for 8 h. 3-MA (5 nM), MitoTEMPO (100 μM), or MCC950 (10 μM) was added to culture medium for 4 h before exposing to contrast media [[24], [25], [26]]. The method of contrast-induced HK-2 cells (20 mgI/ml) was completed as previous described [5,6], and HK-2 cells were collected for use at 72 h after incubating with iohexol.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, macrophage stressinducing protein SESN2 inhibits the NLRP3 inflammasome activation through inducing mitophagy [85]. Recently researches showed that OPTN inhibits the activation of NLRP3 inflammasome by enhancing mitophagy [150], and FUNDC1-mediated mitophagy suppresses hepatocarcinogenesis via inhibition of inflammasome activation [151]. Above studies show that mitophagy inhibits NLRP3 inflammasome activation by eliminating damaged mitochondria.…”
Section: Mitophagy and Inflammasomementioning
confidence: 94%
“…Moreover, MAMs are also responsible for mitophagy activation as previously described, meaning that MAMs might regulate NLRP3 inflammasome activation by mitophagy. This theory is also supported by a study by Chen et al, in which they showed that enhanced mitophagy could inhibit the NLRP3 inflammasome activation of renal tubular cells in DKD [ 154 ]. Overall, the preceding information validates the permissive role of mitochondria in tubular injury, which acts as an upstream mediator of NLRP3 activation via cooperation with MAMs.…”
Section: Mams and Inflammationmentioning
confidence: 54%